Information System Using The Web For Garbage Bank Transactions (A Case Study of TPS 3R Sido Makmur, Sidoharjo, Pacitan) - Tamara Maharani; Dhodit Rengga Tisna (LPPM Universitas An Nuur, 2022)
The construction of a web software, is expected to assist users in processing data and obtaining information quickly, precisely and as needed, along with technological developments, especially in the field of information technology This application contains the Garbage Bank Information System at TPS 3R Sido Makmur, Sidoharjo village, Pacitan district. Application is built using HTML, PHP and CSS programming. The database used is MySQL. With this information system, it is expected to be able to handle transactions that run at the waste bank and provide data reports needed by system users, so that the waste bank work process is more effective and efficient.